Medical care of tennis players by country - Wood, T. (British Journal of Sports Medicine, 2006)
Over 200 national tennis federations are affiliated to the International Tennis Federation, the governing body for tennis. The standard of medical care provided by each national federation to its tennis players various enormously. The biggest challenge in providing this medical care is that it has to be achieved within a frame work that is totally controlled by coaches and the ATP/WTA/ITF tournament schedule.